Radiation characterization at laser wakefield accelerators - Clawson, Soren Baines, author; Brandl, Alexander, advisor; Johnson, Thomas, committee member; Mooney, Michael, committee member; Mann, Jenelle, committee member (Colorado State University. Libraries, 2025)
Laser wakefield acceleration (LWFA) is a rapidly evolving technology that enables the compact acceleration of electrons to relativistic velocities using intense, high repetition laser pulses in plasma. These high-energy electrons interact with surrounding materials to produce complex, pulsed radiation fields composed of bremsstrahlung photons, neutrons, and in some cases, exotic mesons and leptons. Accurately characterizing these radiation environments is essential for radiation protection and facility safety planning in LWFA environments. This thesis presents a computational framework for estimating the spectral distributions of secondary radiation generated by monoenergetic electron beams. The geometric basis of the simulations presented is of the Advanced Beam Laboratory, room 103, at Colorado State University. Using the Monte Carlo N-Particle (MCNP) transport code, a two-stage simulation approach was developed to mitigate inefficiencies in electron transport. In the first stage, electron interactions in a tungsten target were used to construct angle- and energy-resolved photon spectra, as photons are the primary generator of mesons, leptons, and neutrons. These photon distributions were then used as sources in secondary simulations to estimate effective dose from photons and neutrons throughout the laboratory environment. Near the main laboratory entrance, for a 10 pC bundle of accelerated electrons accelerated between 100 MeV and 10 GeV, combined photon and neutron effective doses are found to range between 2.69 pSv and 506 pSv. This method accounts for directional asymmetries in emission, uncertainty propagation, and applies fluence-to-dose conversion factors for photon and neutron fluences at point detectors. Results include dose estimates per incident electron as a function of beam energy. This study supports the development of predictive dose models and provides data-driven tools for the for the design of radiological controls in future high-energy LWFA experiments.
Keywords: wakefield; health physics